Variability in competitive performance of elite track cyclists - Flyger, N. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
This study calculated the individual variation in performance times for cyclists competing in international track cycling events as Typical Error and attempted to express that variation in terms of power. Performance times were collated from six international events during the 2005/06 UCI Track Season and log transformed. Typical Error was calculated via the back transformation of the RMSE from a two-way ANOVA excluding the interaction term. The average Typical Error over all events was 1.0% (0.8 - 1.3 95% CL). Theoretically when performance is expressed as average power, the variation is approximately 3%. Modelling of power output for typical male and female pursuit cyclists appears to confirm this relationship under typical race conditions. These results can be used to assess the suitability of a field-based aerodynamic test for measuring the smallest worthwhile performance enhancing change in drag, whether a cyclist has shown worthwhile improvements in power during a laboratory performance test or in performance time during a competitive season.